A Novel H2O2 Generator for Tumor Chemotherapy-Enhanced CO Gas Therapy - Li, Yang; Liu, Zeming; Zeng, Weng; Wang, Ziqi; Liu, Chunping; Zeng, Ning; Zhong, Keli; Jiang, Dazhen; Wu, Yiping (Frontiers in Oncology, 2021)
CO gas therapy is a promising cancer treatment. However, gas delivery to the tumor site remains problematic. Proper tunable control of CO release in tumors is crucial to increasing the efficiency of CO treatment and reducing the risk of CO poisoning. To overcome such challenges, we designed ZCM, a novel stable nanotechnology delivery system comprising manganese carbonyl (MnCO) combined with anticancer drug camptothecin (CPT) loaded onto a zeolitic imidazole framework-8 (ZIF-8). After intravenous injection, ZCM gradually accumulates in cancerous tissues, decomposing in the acidic tumor microenvironment, releasing CPT and MnCO. CPT acts as a chemotherapy agent destroying tumors and producing copious H2O2. MnCO can react with the H2O2 to generate CO, powerfully damaging the tumor. Both in vitro and in vivo experiments indicate that the ZCM system is both safe and has excellent tumor inhibition properties. ZCM is a novel system for CO controlled release, with significant potential to improve future cancer therapy.